RANCANG BANGUN SIMULATOR SISTEM TREATMENT BAHAN BAKAR BIODISEL B20 PADA TANKI INDUK BAHAN BAKAR KRI YOS SUDARSO - Hadi Prasutiyon; Arif Winarno; Edlyn Criptosan (ROTOR, 2020)
Biodiesel B20 is a mixture of 80% fossil diesel fuel and 20% biofuel. When using B20, the fuel has problems in the form of jelly or mud deposition, so it needs to be overcome by treatment. The treatment that is used today uses a circulation pump but has shortcomings and is not efficient so it needs to be modified using a stirrer. In this research, an analysis of the stirrer treatment using ANSYS software simulation method was carried out to determine the change of sediment before and after stirring, with stirring speed 150 rpm. The use of a stirrer simulation is to make 2 simulation models in the main tank as the largest volume and the daily tank as the smallest volume aims to determine the differences in the results of stirring in the largest and smallest tank.. At the time of stirring, the result is a decrease in sediment from 0 minutes to 4 minutes, then 4 minutes to 8 minutes, then 8 minutes to 12 minutes, then 12 minutes to 16 minutes, then 16 minutes to 20 minutes the fuel has decreased very much and the sediment is almost gone. When stirring is carried out for 20 minutes, the sediment in the fuel tank has not reached 0% so it needs to be stirred continuously until the deposit is 0%. After the fuel has not settled, the fuel is transferred to the main engine using a transfer pump.